Selection of appropriate retrofitting scheme for level 3 hospitals - Balagtas, Francis Ian A.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Hospitals are considered to be one of the most essential structures in society. It is important that these structures are left standing following a disaster. A study called Metropolitan Manila Earthquake Impact Reduction Study or MMEIRS projected potential building damages in case of a 7.2 magnitude earthquake coming from the West Valley Fault System. In order to mitigate the projected damages, seismic retrofitting can be used to increase the seismic capacities of the structures. The study aims to select an appropriate retrofit scheme for non-retrofitted hospitals. The study focuses on visual investigation and seismic risk assessment of structures in order to determine the typology of the structure and its vulnerabilities. Using the typology and vulnerabilities of the structures, a series of checks will be done in order to help choose an appropriate retrofit scheme for the building. The study first investigated three retrofitted hospitals in order to determine the typology and common deficiencies and the corresponding retrofit scheme for them. The three retrofitted hospitals that were investigated were Rizal Medical Center, Philippine Children's Medical Center and National Children's Hospital. The non-retrofitted hospital examined in the study is Philippine Orthopedic Center. After the determination of the typology and vulnerabilities of the hospital, a series of checks were made and the appropriate retrofitting method proposed by the study is global retrofitting by using Steel Bracing Systems with the support of FRP Wrapping on the joints.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Hospital buildings -- Earthquake effects; Buildings -- Retrofitting